Com as próprias mãos: etnografia das artes marciais e da defesa pessoal no treinamento policial militar - Pires, Lucas Alexandre (2018)
This dissertation is based on an ethnographic study on the conversion of martial arts into techniques of hand-to-hand combat and self-defense, applied to military and police training. Martial arts appear in the field with military police subjects such as technologies and war artifacts whose immersion in their practices forge bodies and transform people through processes that directly affect how they understand and experience violence and the use of force. Thus, I report some experiences in martial training, outlining a general picture of its impact on the lives of its practitioners, using my body as an ethnographic tool. Later, I discuss the tense relationship between an anthropologist, who seeks to reveal unsuspected relationships between his subjects and military institutions, which camouflage information, hamper access to the barracks reality, and attempt to frame researcher and research in their own interests. I also perform an ethnohistorical exercise on the relationship between martial arts and military training of different armies around the world, highlighting both the sportification process of militarism and the conversion of sport into military tactics. Finally, I analyze some experiences with military police during instructions of the Personal Defense discipline and in a sporting championship internal to the corporation in order to elucidate the way my interlocutors think and use of martial techniques and their body in their craft. As a conclusion, I understand the martial arts and military training as reflections of the way our society experiences and lives violence, born of its affluence through state action.